Probing Obscured Star Formation in Galaxy Clusters Using JWST Medium-band Images: 3.3 μm PAH Emitter Sample in A2744 - Cheng, Cheng; Wang, Xin; Liang, Piaoran; Sun, Fengwu; Ibar, Edo; Brinch, Malte; Yan, Haojing; Huang, Jia-Sheng; Li, Jun; Molina, Juan (The Astrophysical journal. Supplement series, 2025)
Star-forming galaxies in galaxy clusters play a crucial role in understanding the advanced stages of galaxy evolution within dense environments. We present a sample of 3.3 μ m polycyclic aromatic hydrocarbon (PAH)-bright galaxies in the A2744 galaxy cluster. Using F430M medium-band images, we select PAH emitters in the galaxy cluster, which capture the 3.3 μ m PAH emission at the redshift of A2744. Our multiwavelength study demonstrates consistent star formation rates (SFRs) derived from PAH emission and spectral energy distribution fitting, indicating that the 3.3 μ m PAH flux estimated from the medium-band image alone can reveal the entirety of star formation, immune to dust obscuration. We find that the PAH emitters are located in relatively low-mass surface density regions of A2744, with SFRs aligning with the field star-forming main sequence at z = 0.3. The PAH emission morphologies show more asymmetry than that of the F444W image when the asymmetry index is >0.4. With these results, we suggest that these star-forming galaxies in A2744 are in the stage of falling into the cluster from the field, and have not been quenched yet. We further explore a potential link between these galaxies and cosmic filaments being accreted onto the cluster, which may channel gas inflows to fuel star formation. JWST medium-band imaging provides a powerful new tool for identifying heavily dust-obscured star-forming populations. Future H I and low- J CO observations should be prioritized to resolve the cold gas kinematics and star formation processes in these systems, which would directly test the role of environmental stripping versus filamentary gas supply.